Fault-tolerant for Electric Vehicles Drive System Sensor Failure - Zhang Liwei; Xu Chen; Liu Jie; Wu Jialong (Institute of Advanced Engineering and Science, 2013)
When EV failure happens, it needs to take some fault-tolerant method to ensure people’s safety. When the current sensor and speed sensor are out of work, the software fault-tolerant control algorithm switching strategy can be used. This paper has done theoretical analysis of the rotor field-oriented vectoe control algorithm into the open loop constant V/F control algorithm, and the phase angle compensation method is used to reduce the shock of current and torque, and simulation is done in MATLAB/Simulink. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3426